Late-in-life motherhood: Ethico-legal perspectives on the postponement of childbearing and access to artificial reproductive technologies - Goold, I (Oxford University Press, 2017)
Many women postpone childbearing until later in life and face infertility as a result. Social attitudes are often critical of whether these women should receive assisted reproductive technologies. These attitudes include blame for choosing to “have it all” with a career and a family, ridicule of older women becoming mothers, and views about the inappropriate use of health resources in support of supposed lifestyle choices. Ethically speaking, however, there is little support for restricting such infertility treatment or for funding it for younger women while withholding it from others. Neither choice nor natural aging can be defended as a ground on which to distinguish between older and younger women with respect to the receipt of care.